Estimation model of the diesel engine fuel system with an electromechanical device to intensify fuel supply - Ivanov, Oleg; Kharak, Ruslan; Kostenko, Olena; Arendarenko, Volodymyr; Nazarenko, Oleksii; Pushka, Alexander; Sarana, Victor (Eastern-European Journal of Enterprise Technologies, 2019)
The key directions of the development and improvement of the fuel supply system for internal combustion engines with ignition from compression of the fuel/air mixture were pointed out. The need for the comprehensive implementation of electromechanical principles of fuel injection control in accordance with the various conditions of diesel engines operation was proved. The relevance of further development and modernization of the hydromechanical fuel systems on the background of ever-increasing interest in their electro-controllable analogues was highlighted. The unused potential possibilities of hydromechanical fuel equipment to improve the conditions of the fuel supply process were listed. To intensify fuel injection, it was proposed to use the electromechanical device that is mounted in the fuel discharge pipeline and modifies the phase-amplitude characteristic of the wave process of propagation of a single supplying pulse between the high-pressure fuel pump and the hydromechanical nozzle. We highlighted the important aspects of the procedure for constructing the calculation model of the switchgear-type fuel system of direct action with a new device for fuel supply intensification. It was proposed to consider the fuel injection process at some stages, taking into consideration the characteristics of functioning of a particular hydraulic node of the fuel system, including the proposed technical means of intensification. The systems of differential and analytical equations that make it possible to perform mathematical modeling of the process of propagation and mutual influence of the pressure waves in the pressure-pumping tract were presented. The resulting systems make it possible to obtain characteristics of a change in hydraulic pressure in different fuel volumes, the kinematics of motion of shut-off elements in a high-pressure pump and nozzle, etc. In the course of a comparative study, carried out on the basis of the presented calculation model, the fuel injection process for the standard and improved fuel system for a turbo-diesel, a significant improvement of the injection quality by a large number of indicators was revealed. According to the results of calculations, the existence of high-rate character of increasing and decreasing of injection pressure at the initial and final phase of the process of fuel supplyi to the cylinders of a diesel engine is observed. It was noted that the rate of pressure change can reach 170 MPa/deg, maximum, and average injection pressure increases up to 75 MPa and 30...40 MPa, respectively. Calculation studies were carried out with the employment of the numerical method of integration – the Adams interpolation method, the choice of which is caused by the necessity of obtaining consistent solutions when solving the described systems of differential equations, which belong to the category of the rigid